Languages and language situation of Southeast Asia - Omar, Asmah Haji (Journal of Modern Languages, 2017)
The Southeast Asian region is indeed a linguistically diverse one. Diversity is clearly seen in the membership of indigenous languages within language stocks and families. In terms of language policy adopted by the various countries in modern limes) there arc points of similarity as well as divergence brought about by historical processes as well as the philosophies adopted by them for the good of their own peoples.